Donor notification of permanent deferral: a qualitative study on the perceptions and practices of notifier and blood donor in Mexico - V Moisés Serrano-Delgado; Edith Valdez-Martínez; Horacio Márquez-González (BMC, 2022)
Abstract Background Informing about permanent deferral requires a process that links the notifier with the donor in a particular way. Little is known about the type of information and how it is disclosed to the donors. The current study aimed to examine perceptions and practices of notifier and blood donor within the framework of the notification process of permanent deferral and from the perspective of the notifier-blood donor relationship. Methods A qualitative study with in-depth interviews. The participants were 13 notifiers and 25 permanently deferred donors. Participants were recruited from a national blood bank and a state's blood bank. The entire dataset/narratives were analysed using the method of thematic analysis. Results The disclosure of permanent deferral was understood as a matter of disclosing the serological test results and their medical meaning along with a concise explanation of the deferral status with regard to future blood donation and the plan to be followed. The notifiers preferred to act in accordance with the standard protocol despite acknowledging the adverse psychological and social effects to which donors are exposed when they are informed of the possible disease and the consequent permanent deferral. Donors described a variety of psychological and social affectations. They valued honesty in the communication, the clarity of the information provided and a greater involvement of the notifier. Conclusion Even though the notification process does not imply that medical care is being offered to donors, the notifier is the administrator of the well-being of the donor. Notification must not be considered as something apart from care, since it is intimately related to the health of each of the donors and their medical care.